Shaping the archive in late medieval England : history, poetry, and performance - Sarah Elliott Novacich (Cambridge studies in Medieval literature, 2017)
"Sarah Elliott Novacich explores how medieval thinkers pondered the ethics and pleasures of the archive. She traces three episodes of sacred history - the loss of Eden, the loading of Noah's ark, and the Harrowing of Hell - across works of poetry, performance records, and iconography in order to demonstrate how medieval artists turned to sacred history to think through aspects of cultural transmission. Performances of the loss of Eden blur the relationship between original and record; stories of Noah's ark foreground the difficulty of compiling inventories; and engagements with the Harrowing of Hell suggest the impossibility of separating the past from the present. Reading Middle English plays alongside chronicles, poetry, and works of visual art, Shaping the Archive in Late Medieval England considers how poetic form, staging logistics, and the status of performance all contribute to our understanding of the ways in which medieval thinkers imagined the archive"--